The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0004-27302008000300001
|View full text |Cite
|
Sign up to set email alerts
|

Hiperglicemia e doença cardiovascular podem coexistir

Abstract: Expressões como "diabetes é uma doença vascular, o paciente com diabetes é um coronariopata em potencial, pacientes com diabetes têm o mesmo risco em desenvolver um evento cardiovascular quando comparados com não-diabéti-cos que já tiveram um infarto do miocárdio" têm sido comumente utilizadas e cada vez mais difundidas. Realmente tem sido recomendado que os pacientes com diabetes tipo 2 sejam considerados portadores de doença coronariana e como tal devam ser tratados, incluindo, por exemplo, metas mais rígida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Estimates show that the global number of T2DM patients will reach about 366 million in 2030 (1). T2DM leads to several macro and microvascular complications related to long-term damage and various organsystem failure (2). In this regard, several studies have indicated that T2DM triggers oxidative stress by the production of free radicals and a reduction in antioxidant status (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates show that the global number of T2DM patients will reach about 366 million in 2030 (1). T2DM leads to several macro and microvascular complications related to long-term damage and various organsystem failure (2). In this regard, several studies have indicated that T2DM triggers oxidative stress by the production of free radicals and a reduction in antioxidant status (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Lesão maior do que 70% e não obstruída 33,8% 2412,7% 919,7% (14) Artéria obstruída 28,2% 2025,4% 1811,3% (8)…”
Section: Discussionunclassified
“…Está presente em 25 a 50% dos pacientes admitidos com IAM. 8,9,[11][12][13][14][15] O conjunto de alterações a nível celular, tecidual e sistêmico (necrose celular, acidose celular e sistêmica, entre outros) provocado pela hiperglicemia explica a permanência prolongada no hospital e maior morbimortalidade. 15,16 O risco de complicações hospitalares em não diabéticos e diabéticos com IAM ocorreram com valores de glicemia, respectivamente, maiores que 110 e maiores ou iguais a 180 mg/dl no estudo de Góis e Capes e cols.…”
Section: Introductionunclassified
“…The atherosclerosis in diabetics is more severe, appears with greater frequency, and occurs earlier when compared with healthy individuals, increasing the risk of cardiac infarction in those diabetic individuals [6].…”
Section: Introductionmentioning
confidence: 99%